2016
DOI: 10.1038/npp.2016.151
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Brain-Wide Activity Dynamics by Dopaminergic Neurons

Abstract: Several neuropsychiatric conditions, such as addiction and schizophrenia, may arise in part from dysregulated activity of ventral tegmental area dopaminergic (TH) neurons, as well as from more global maladaptation in neurocircuit function. However, whether TH activity affects large-scale brain-wide function remains unknown. Here we selectively activated TH neurons in transgenic rats and measured resulting changes in whole-brain activity using stimulus-evoked functional magnetic resonance imaging. Applying a st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 77 publications
(95 reference statements)
9
65
1
Order By: Relevance
“…Similarly, recent fMRI studies employing optogenetics to stimulate midbrain dopamine neuron activity reported CBV and BOLD signal increases in rat striatum (Decot et al 2016; Ferenczi et al 2016; Lohani et al 2016). …”
Section: Discussionmentioning
confidence: 82%
“…Similarly, recent fMRI studies employing optogenetics to stimulate midbrain dopamine neuron activity reported CBV and BOLD signal increases in rat striatum (Decot et al 2016; Ferenczi et al 2016; Lohani et al 2016). …”
Section: Discussionmentioning
confidence: 82%
“…This serves one of two functions: (1) To increase the activity of downstream neurons in driving behavior and (2) Increasing the strength of these specific inputs via changes in plasticity. This can occur in all of the projection regions of the VTA, has been seen in the PFC, NAc, and amygdala, and gives further support that these initial dopaminergic changes can induce widespread circuit dysfunction in a range of circuits across the brain to drive maladaptive behaviors (Decot et al, 2017). …”
Section: The Neural Circuits Controlling Motivated Behaviors and Thmentioning
confidence: 80%
“…This is a critical consideration as these types of changes prevent further learning-induced plasticity and can drive compulsive behaviors. However, this is even more important in the context of other glutamatergic circuits across the brain, where changes in striatal circuits lead to more widespread alterations in other brain regions (Baler and Volkow, 2006; Decot et al, 2017; Kalivas and Volkow, 2005; Koob and Volkow, 2016; Moeller et al, 2010). …”
Section: The Neural Circuits Controlling Motivated Behaviors and Thmentioning
confidence: 99%
“…Given that the electrodes are estimated to be sensitive to changes in signal over approximately a 400μm sphere around the electrode [53,54], it is plausible that the signals we recorded here could have been influenced by RPE-like patterns of dopamine release [55]. Several recent papers have shown that optogenetic stimulation of dopamine neurons can have widespread influence on forebrain BOLD signals [56][57][58]. However, direct evidence for this link is currently lacking, and a recent study comparing patterns of BOLD signals with dopamine release in humans found indications of uncoupling between the measures [59].…”
Section: Discussionmentioning
confidence: 96%